'A matter of love': L. V. Randall (1893–1972), Montreal collector and academic visionary. (5th February 2021) - Herman, Nicholas
Abstract: This article examines the career and collection of Lewis V. Randall (1893–1972), a German-born Jewish banker turned Montrealer and amateur art historian. Though virtually forgotten today, Randall assembled the finest collection of Renaissance art ever held in Canada. This ensemble included drawings by Leonardo, Dürer, Patinir, Schongauer, Cranach, Rembrandt and Bosch, as well as manuscript illuminations, sculptures, panel paintings and stained glass. After the Second World War, Randall founded the art history department at the University of Montreal. Drawing on his extensive network of friends, which included Erwin Panofsky and André Chastel, he assembled a brilliant but short-lived cohort of francophone scholars around the fledgling department.